Clinicopathologic features and prognostic factors of diffuse sclerosing variant of papillary thyroid carcinoma: a populationbased analysis - Wang, Yunjun; Guan, Qing; Xiang, Jun; Li, Duanshu (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Background: The diffuse sclerosing variant (DSV) is an aggressive and rare subtype of papillary thyroid carcinoma (PTC). The present study aims to analyze its clinicopathological features and prognosis and compare these findings with classical PTCs. Methods: Data were extracted from the Surveillance, Epidemiology, and End Results (SEER) database (2004–2013), and were retrospectively analyzed to compare clinicopathological characteristics between DSVPTCs and classical PTCs. Survival was analyzed using the Kaplan-Meier method, and the log-rank test was used to determine if differences in survival were statistically significant. Results: In total, 331 cases of DSVPTC and 63,659 cases of classical PTC were included. DSVPTCs had a higher proportion of women and young patients, and presented higher rates of larger tumor size, multifocality, extrathyroidal extension (ETE) and lymph node metastasis than classical PTCs. Total thyroidectomy, neck dissection and radioiodine therapy were more frequently conducted in DSV patients. The 5-year and 10-year cancer-specific survival rates were significantly lower in the DSV group (97.6% and 97.6%, respectively). DSV patients with risk factors including ≥55 years of age, lateral neck metastasis, tumor diameter ≥2 cm, ETE and distant metastasis developed a poorer prognosis. The rate of lateral neck metastasis (28.7%) was significantly higher in the DSV group, and DSV patients with lateral neck metastasis suffered a worse prognosis. Conclusions: DSVPTC is an aggressive subtype with a worse prognosis. Total thyroidectomy and prophylactic central neck dissection followed by radioiodine therapy are more likely to be performed in patients with DSV. Lateral neck dissection should be given full consideration in DSVPTC patients with such predictors as ≥55 years of age, male, ≥2 cm tumor size and ETE.